2019
DOI: 10.22330/he/34/093-103
|View full text |Cite
|
Sign up to set email alerts
|

Chewing on gum alters the expression of contagious yawning

Abstract: The motor action pattern of yawning enhances neurovascular circulation, which appears to function in cooling the brain and promoting adaptive behavioral outcomes linked with arousal and state change. Here, the authors tested whether chewing on gum, which induces similar mandibular contractions and temporarily increases alertness, alters the expression of yawning. Participants were assigned to either a control, mint, or gum condition and instructed to watch a contagious yawning stimulus in the laboratory. Yawni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Since the action patterns of both yawn types appear indistinguishable, the neurological mechanisms governing yawn contagion are likely mediated by the same physiological variables affecting patterns of spontaneous yawning. In support of this view, and consistent with the hypothesis that the motor action pattern of yawning evolved to increase arousal and state change 1 , 84 via intracranial circulation and brain cooling 85 , 86 , socially-elicited forms of contagious yawning can be modulated by different methods of breathing 48 , time of day 74 , cooling/heating to the surface of forehead and neck 48 , 78 , chewing on gum 76 , ambient temperature variation and seasonal climactic conditions 15 , 73 , 77 , and acute physical stress 75 . Collectively these studies support the view that spontaneous and contagious forms of yawning share fundamental mechanistic pathways 87 .…”
Section: Discussionsupporting
confidence: 75%
“…Since the action patterns of both yawn types appear indistinguishable, the neurological mechanisms governing yawn contagion are likely mediated by the same physiological variables affecting patterns of spontaneous yawning. In support of this view, and consistent with the hypothesis that the motor action pattern of yawning evolved to increase arousal and state change 1 , 84 via intracranial circulation and brain cooling 85 , 86 , socially-elicited forms of contagious yawning can be modulated by different methods of breathing 48 , time of day 74 , cooling/heating to the surface of forehead and neck 48 , 78 , chewing on gum 76 , ambient temperature variation and seasonal climactic conditions 15 , 73 , 77 , and acute physical stress 75 . Collectively these studies support the view that spontaneous and contagious forms of yawning share fundamental mechanistic pathways 87 .…”
Section: Discussionsupporting
confidence: 75%
“…An extension of this work also showed that cooling of the carotid blood supply, which is sufficient to decrease temperature at the superiomedial orbital area (i.e., the brain temperature tunnel; Abreu, Haddidan, Hott, Assis, & Silverman, 2010), significantly diminishes both the urge to yawn and overall contagious yawning frequency (Ramirez, Ryan, Eldakar, & Gallup, 2019). Moreover, Gallup & Engert (2019) recently demonstrated that chewing on gum significantly decreases the rate, frequency, and duration of contagious yawning among college students. Given that the mandibular contractions of gum chewing increase cerebral blood flow (Hasegawa, Ono, Hori, & Nokubi, 2007), these results further support the hypothesized brain cooling and neurovascular circulatory functions of spontaneous yawning.…”
Section: Introductionmentioning
confidence: 62%
“…These findings provide converging evidence that gum chewing inhibits the expression of yawning. Recently, Gallup & Engert (2019) found that chewing on gum Human Ethology, 35, 67-74 reduced the rate, frequency, and duration of contagious yawning among college students in the laboratory. Similar to the extended gaping of the jaw during yawning, the mandibular contractions of chewing on gum are known to increase cerebral blood flow (Hasegawa et al, 2007), and therefore this behavior may act to stifle the mechanism(s) driving the abnormal yawning.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 Other documented effects that cannot be explained by the airway hypothesis (1) The influence of nasal vs. oral breathing and carotid artery and forehead temperature on yawn frequency [23,24] (2) The link between yawn duration and brain size after accounting for body size [5] (3) How chewing on gum decreases, rather than increases, yawning [25,26] (4) The connection between abnormal yawning and thermoregulatory dysfunction in the absence of breathing problem [27] (5) Why there is a reduction in yawning frequency with senescence [28], as airway mechanics and lung function decline with age [29] (6) The fact that fish, which have a completely different oxygenation system, also yawn [30]…”
mentioning
confidence: 99%